Konsep Dasar dan Tantangan Manajemen Likuiditas pada Perbankan Syariah - Muhsyi Alyah; Susi Susi; Asni Gusmiarni; Bustan Ramli (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2026)
Liquidity management is an important aspect in maintaining the operational stability of Islamic banking. Inadequate liquidity management can affect a bank’s ability to fulfill its short-term obligations and reduce public trust in banking institutions. This study aims to examine the basic concepts of liquidity management, liquidity management practices, and the various challenges faced by Islamic banks in maintaining financial stability. The study employed a qualitative method using a literature review approach through the examination of various sources, including books, scientific journals, and research articles relevant to the topic. The collected data were analyzed descriptively to obtain a systematic understanding of liquidity management in Islamic banking. The findings indicate that liquidity management in Islamic banks is carried out through asset and liability management, fund collection, financing distribution, and the implementation of GAP management. In addition, Islamic banking faces several challenges, including the limited availability of Islamic money market instruments, imbalance between assets and liabilities, risks of massive customer withdrawals, and changes in economic conditions and regulations. Therefore, adaptive liquidity management strategies based on prudential principles are required to maintain operational stability and ensure the sustainability of Islamic banking institutions.